2021
DOI: 10.5603/cj.a2021.0022
|View full text |Cite
|
Sign up to set email alerts
|

Patient counselling service with the use of pictograms as the example of pharmacist intervention to improving compliance and medicine safety

Abstract: Background: Pharmaceutical pictograms have been designed to help communicate medication instructions to patients. Pictograms used within a patient counseling service can significantly improve medication compliance and adherence. The study aimed to assess the improvement of adherence to therapy with the use of pictogram intervention in comparison to standard pharmacy practice in community pharmacies. Methods: Pictograms informing about the proper way of using metoprolol prolonged release tablets were designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
7
0
5
Order By: Relevance
“…This study demonstrated that pictogram interventions reduced dosing errors among mothers with poor health literacy when administering liquid medication to children by approximately 48 to 54% and improved the mothers' understanding of dosing (Chan et al, 2015;Patidar et al, 2021). Therefore, pictograms are being utilized in patient counselling within pharmacy settings to enhance compliance and medication safety (Merks et al, 2021;Vaillancourt et al, 2019). Overall, the present results revealed that the majority of the respondents agreed that pictograms should be used in medication packages and leaflets.…”
Section: Discussionmentioning
confidence: 95%
“…This study demonstrated that pictogram interventions reduced dosing errors among mothers with poor health literacy when administering liquid medication to children by approximately 48 to 54% and improved the mothers' understanding of dosing (Chan et al, 2015;Patidar et al, 2021). Therefore, pictograms are being utilized in patient counselling within pharmacy settings to enhance compliance and medication safety (Merks et al, 2021;Vaillancourt et al, 2019). Overall, the present results revealed that the majority of the respondents agreed that pictograms should be used in medication packages and leaflets.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies have shown that pharmacists are willing to extend their services to play a greater role in public health. The NMS has been also implemented in Poland [ 33 , 34 ], where this service was a part of the project “Closer to the Patient”. The findings demonstrated that the use of pharmaceutical intervention in the study group translated into improved adherence to medical instructions regarding correct pharmacotherapy [ 35 ]…”
Section: Challenges To Nms Implementationmentioning
confidence: 99%
“…Pictograms could help patients to adhere to medical advice and reduce the potential risks or errors associated with the misuse of medications. Merks et al [ 19 ] demonstrated that pictograms significantly helped patients not to omit doses, not to crush tablets, to use a proper number of tablets per day and to use tablets at the proper time. Health behaviors contribute to the development of good habits throughout the patient’s life.…”
Section: Introductionmentioning
confidence: 99%